Characteristics of fecal metabolic profiles in patients with irritable bowel syndrome with predominant diarrhea investigated using 1H‐NMR coupled with multivariate statistical analysis. Issue 6 (3rd March 2020) - Lee, Jae Soung; Kim, Seok‐Young; Chun, Yoon Shik; Chun, Young‐Jin; Shin, Seung Yong; Choi, Chang Hwan; Choi, Hyung‐Kyoon
Abstract: Background: Gut microbiota are known to be closely related to irritable bowel syndrome (IBS). However, not much is known about characteristic fecal metabolic profiles of IBS. We aimed to characterize fecal metabolites in patients with IBS with predominant diarrhea (IBS‐D) using 1 H‐nuclear magnetic resonance ( 1 H‐NMR) spectroscopy. Methods: In this study, we enrolled 29 patients diagnosed with IBS‐D according to the Rome IV criteria, 22 healthy controls (HC) and 11 HC administered laxatives (HC‐L) in the age group of 20‐69 year. The usual diet of the patients and HC was maintained, their fecal samples were collected and investigated by NMR‐based global metabolic profiling coupled with multivariate statistical analysis. Results: We detected 55 metabolites in 1 H‐NMR spectra of fecal samples: four amines, 16 amino acids, six fatty acids, eight organic acids, three sugars, and 18 other compounds. Orthogonal partial least square‐discriminant analysis derived score plots showed clear separation between the IBS‐D group and the HC and HC‐L groups. Among the 55 metabolites identified, we found five disease‐relevant potential biomarkers distinguishing the IBS‐D from the HC, namely, cadaverine, putrescine, threonine, tryptophan, and phenylalanine. Conclusions: The patients with IBS‐D were clearly differentiated from the HC and HC‐L by fecal metabolite analysis using 1 H‐NMR spectroscopy, and five fecal metabolites characteristic of IBS‐D were found. The findings of this study could be used to develop alternative and complementary diagnostic methods and as a source of fundamental information for developing novel therapies for IBS‐D. Abstract : Fecal metabolic profiling of patients with IBS‐D was clearly differentiated from that of healthy controls administered laxatives or not. Five disease‐relevant potential biomarkers (cadaverine, putrescine, threonine, tryptophan, and phenylalanine) were found in patients with IBS‐D, excluding the effects of fast colon transit. It provides fundamental information for developing novel therapies for IBS‐D.